2021
DOI: 10.1039/d1py00483b
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly behavior of oligo(ethylene glycol) substituted polycaprolactone homopolymers

Abstract: Amphiphilic homopolymers are gaining importance due to their easy synthesis compared to copolymers and their ability to assemble into various nanostructures. The majority of reported amphiphilic homopolymers have a non-biodegradable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…Polycaprolactone (PCL), a member of aliphatic polyesters, has garnered growing attention with extensive applications in the biomedical and pharmaceutical fields and as packaging materials owing to the promising biocompatibility and degradability. Despite its many advantages and commercial availability, PCL still has inherent limitations for practical applications due to its low melting processing temperature and low hydrophilicity. Massive efforts have been devoted to the development of functional PCLs via substitution on PCL or incorporation of heteroatoms to the main chain. For example, poly­(1,5-dioxepan-2-one) (PDXO) containing both ester and ether functionalities in the polymer backbone was synthesized, and it demonstrated enhanced hydrophilicity compared with PCL. ,,, However, the complete amorphousness of PDXO limits its potential application scope. Besides, sulfur-containing polymers have established a variety of intrinsic merits and potential applications because they possess outstanding optical and electrical features and exhibit potential coordinating ability to heavy metal ions. The introduction of sulfur atoms into PCL to generate poly­(1,4-oxathiepan-7-one) (POTO), an analogue of PDXO, has been reported to display a slightly higher glass transition temperature ( T g ) than PDXO.…”
Section: Introductionmentioning
confidence: 99%
“…Polycaprolactone (PCL), a member of aliphatic polyesters, has garnered growing attention with extensive applications in the biomedical and pharmaceutical fields and as packaging materials owing to the promising biocompatibility and degradability. Despite its many advantages and commercial availability, PCL still has inherent limitations for practical applications due to its low melting processing temperature and low hydrophilicity. Massive efforts have been devoted to the development of functional PCLs via substitution on PCL or incorporation of heteroatoms to the main chain. For example, poly­(1,5-dioxepan-2-one) (PDXO) containing both ester and ether functionalities in the polymer backbone was synthesized, and it demonstrated enhanced hydrophilicity compared with PCL. ,,, However, the complete amorphousness of PDXO limits its potential application scope. Besides, sulfur-containing polymers have established a variety of intrinsic merits and potential applications because they possess outstanding optical and electrical features and exhibit potential coordinating ability to heavy metal ions. The introduction of sulfur atoms into PCL to generate poly­(1,4-oxathiepan-7-one) (POTO), an analogue of PDXO, has been reported to display a slightly higher glass transition temperature ( T g ) than PDXO.…”
Section: Introductionmentioning
confidence: 99%
“…TBD was reported as an efficient ROP catalyst for γ-amide functionalized ε-CL monomers. 14,15 Fully biodegradable amphiphilic diblock copolymers PBnCL-b-PME 3 PyCL, PCL-b-PME 3 PyCL, and PCL-b-PME 3 CL (control) were prepared by sequential monomer addition (Scheme 2b and c) with a experiment ratio of 45 to 55 between hydrophobic and hydrophilic monomers. The γ-functionalized ε-CL monomers γ-ME 3 CL and γ-BnCL were synthesized following the reported procedure in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…However, those vinyl-based homopolymers are nondegradable. Calubaquib et al 14 reported the micellar self-assembly of biodegradable γ-functionalized PCL homopolymers bearing OEG groups. The monofunctionalized homopolymers bearing only hydrophilic OEG side chains showed high CMC of about 10 −1 g L −1 and are thermoresponsive.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly of homopolymers is related to various factors such as the molecular weight of polymers, 50 polymer concentration, 51 solvent, 52 temperature, 53 pH, 54 additives, 55 etc . Among these, temperature is a convenient factor to access various morphologies.…”
Section: Resultsmentioning
confidence: 99%